Pengaruh Pengawasan Controller dan Iklim Organisasi Terhadap Produktivitas Kerja Staf Ground Handling PT Avia Citra Dirgantara Malang - Ela Rosada Vebrianti; Arif Fakhrudin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The aim of this research is to determine the influence of controller supervision on the work productivity of ground handling staff, to determine the influence of organizational climate on the work productivity of ground handling staff, to find out how much influence controller supervision and organizational climate have on the work productivity of ground handling staff at PT. Avia Citra Dirgantara Malang. The research was conducted on 1 August 2023 – 30 September 2023 at PT. Avia Citra Dirgantara Malang. This research uses quantitative methods by collecting data using questionnaires. The quantitative methods used are validity, reliability, multiple regression, t test, f test, and coefficient of determination tests. The research was conducted at PT. Avia Citra Dirgantara Malang. The results of research based on Tcount results carried out using SPSS software show a Tcount value of 9.635 which is greater than Ttable 1.987 and a significant value of 0.000 which can be interpreted as that controller supervision has a positive effect on the work productivity of PT ground handling staff. Avia Citra Dirgantara Malang. Based on the results, Tcount is -3.582 which is greater than Ttable 1.987 and a significant value of 0.001 which can be interpreted as meaning that the organizational climate has no effect on the work productivity of PT ground handling staff. Avia Citra Dirgantara Malang. Based on the results of the F test, it shows that statistical calculations show a significant P value of 0.000 < 0.05, which means that controller supervision and organizational climate can jointly influence the work productivity of ground handling staff at PT. Avia Citra Dirgantara.